Complete mitochondrial genomes of three mitten crabs, Eriocheir sinensis, E. hepuensis, and E. japonica. (3rd March 2016) - Wang, Jun; Huang, Lei; Cheng, Qixuan; Lu, Guoqing; Wang, Chenghui
Abstract: Taxonomic classification of three mitten crabs ( Eriocheir sinensis, E. hepuensis, and E. japonica ) has long been controversial. In this study, the complete mitogenomes of the three crabs were reported. The three mitogenomes were conserved in the organization of genes with 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and 1 control region. Nucleotide variations among the crabs were identified in both coding and non-coding regions. In addition, variable numbers of tandem repeats in control region were identified in the mitten crabs. The mitogenome sequences provide a valuable resource to elucidate taxonomic relationship and evolutionary history of the three mitten crabs.